Joint Decisions on Household Membership and Human Capital Accumulation of Youths: The role of expected carnings and labour market rationing - Chiara Monfardini; Gianna Claudia Giannelli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2000)
This paper focuses on the youth's decisions on household formation and human capital investment - in further education or work experience - and the factors influencing these choices. While previous studies limited their analyses to decisions concerning the living arrangements and the labour market, the choice set is extended here to take into account other alternatives. The decisions of either remaining in the parental household or going to live with a partner are modelled jointly with those of either entering the labour market (i.e. investing in work experience) or investing in higher (university) education. Using the Bank of Italy 1995 Sample Survey on Italian Households, a multinomial probit model estimates the probabilities of the different pairs of outcomes. The results highlight the crucial role of economic variables in shaping young adults' decisions. Among these, expected lifetime earnings from attending university have the most important impact on the choice of studying and coresiding. Implications for policy stem from the estimated impact of housing and labour market performance variables on young adults' decisions. In particular, a sizeable discouraged worker effect, inducing young people to study when the local unemployment rate is high, is detected. The effect of the cost of housing in delaying young workers' decisions to leave the parental home and form a new household is also remarkable. Two policy experiments are presented. The former measures the impact of housing policies targeted at reducing housing cost on the probability of marriage. The latter measures the extent to which labour policies targeted at reducing youth unemployment would decrease the number of discouraged workers that choose to study.
Keywords: 330